Economic growth and the demand for foreign labor in the oil-exporting and labor-importing states of the Arab Gulf: Case of Oman - Ibtisam Al Abri; Omar Al Hinai; Sara Al Raisi; Abdullah Al Harrasi; Zeyana Al Jabri; Maryam Al Maskari (Cogent Business & Management, 2023)
AbstractDespite the generally swift economic growth in the Arab Gulf countries, they still face a national problem with the unemployment of nationals. Given the relatively large inflow of foreign labor across these countries, it is essential to study the association between foreign labor and economic growth in the short and long terms. This paper examines the relationship between economic growth and demand for labor in Oman, considering separately skilled and unskilled labor as well as hydrocarbon GDP and nonhydrocarbon GDP. Additionally, the study conducts formal tests to determine the direction of short-term and long-term Granger causality among all variables, at both aggregated and disaggregated levels. A total of 18 Auto-Regressive Distributed Lag (ARDL) models are applied to examine these relationships. In the long term, results indicate that both skilled and unskilled labor have a positive effect on GDP. However, these relationships are negative in the short term due to adjustment to a new country and productivity reasons. Moreover, it is found that once economic conditions flourish, there is an increased demand for skilled and unskilled expatriate labor. When looking at non-oil activities, a positive relationship between nonhydrocarbon GDP and total expatriate labor is evident. Specifically, the relationships between nonhydrocarbon GDP and unskilled expatriate labor are highly significant indicating a bidirectional relationship. Ultimately, such verdicts provide an insightful guide to policymakers in Oman and the Arab Gulf countries on labor market correlations and dynamics so as to initiate effective labor market reforms and promote jobs for nationals.